Time to act sustainably: Why can't we wait any longer? - Patrícia de Oliveira Furukawa; Isabel Cristina Kowal Olm Cunha; Mavilde da Luz Gonçalves Pedreira (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to raise reflections on the need for health services and professionals to implement sustainable actions, aiming at their own survival and that of the planet. Methods: reflective essay based on international reports regarding the impact of climate change on people's health and the role of institutions in this context. Results: the article focused on three fundamentals: climate change continues to be a threat to the health and well-being of all beings on Earth; the institutions that should contribute to health are great agents of contamination of the environment and emission of gases that aggravate the greenhouse effect; and there are several benefits for health institutions to act sustainably. Final Considerations: we cannot wait any longer; we must develop policies and management models aimed at environmentally responsible, economically viable, and socially more collaborative healthcare.